2006
DOI: 10.1242/jeb.02137
|View full text |Cite
|
Sign up to set email alerts
|

Forage fibre digestion, rates of feed passage and gut fill in juvenile and adult red kangaroosMacropus rufusDesmarest: why body size matters

Abstract: SUMMARY Using red kangaroos Macropus rufus Desmarest, a large (>20 kg)marsupial herbivore, we compared the digestive capabilities of juveniles with those of mature, non-lactating females on high-quality forage (chopped lucerne Medicago sativa hay) of 43±1% neutral-detergent fibre (NDF)and poorer quality, high-fibre forage (chopped oaten Avena sativahay) of 64±1% NDF. On chopped lucerne apparent dry matter (DM)digestibilities by young-at-foot (YAF) red kangaroos (an age that would normally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 63 publications
4
26
1
Order By: Relevance
“…1; Stevens and Hume 1995;Hume 1999). The kangaroo forestomach is typified by numerous haustrations that likely provide elastic support for physical flexibility in content loads, as was observed here (Table 2), probably facilitating reserve gut capacity under different nutritional circumstances (e.g., Munn and Dawson 2006;. In this study, we found that there was profound phenotypic plasticity of the hindgut, mainly in the proximal and distal colon but probably also in the cecum.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…1; Stevens and Hume 1995;Hume 1999). The kangaroo forestomach is typified by numerous haustrations that likely provide elastic support for physical flexibility in content loads, as was observed here (Table 2), probably facilitating reserve gut capacity under different nutritional circumstances (e.g., Munn and Dawson 2006;. In this study, we found that there was profound phenotypic plasticity of the hindgut, mainly in the proximal and distal colon but probably also in the cecum.…”
Section: Discussionsupporting
confidence: 71%
“…In macropodids, there is a marked separation of small and large particles in the foregut, with smaller particles and solutes exiting the tubiform forestomach faster than larger particles (Dellow 1982;Munn and Dawson 2006). Thus, as intakes of small particles increase, such as in animals receiving pelleted diets (Freudenberger and Hume 1992) or high-quality forage (inferred from ruminants and swine ;Grenet 1989;van Bruchem et al 1991;Robertson et al 1992), more bulk flow of potentially digestible material would pass to the lower gut.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially problematic for juvenile mammals whose mass at weaning is often lower than adult mass and who often have not completed their morphological and physiological development. Incomplete morphological de -velopment can inhibit the handling of larger-sized prey items (Brito 2004, La Croix et al 2011 or the digestion of specific prey items (Munn & Dawson 2006), thus narrowing the choice of suitable prey, which in turn leads to differences in resource utilisation and foraging habitat between juveniles and adults (Wikelski & Trillmich 1994. Physiological limits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Animals were kept in individual cages and were handled carefully under standard conditions of 12h dark light cycle in temperature 24±3ºC and relative humidity of 50-60%. Before commencing this experiment, all animals were injected with 0.1mL/Kg body weight ivermectin (s.c.) [19] to eradicate endo and ecto-parasites, followed by a week of adjustment period. This treatment, with ivermectin, will help to minimize the interference of parasites in the course of the study.…”
Section: Animalsmentioning
confidence: 99%